Aplikasi Rasio Keuangan untuk Memprediksi Laba pada Perusahaan Properti yang Go Publik di Bursa Efek Jakarta - Sunarjanto, N. Agus; Anggraeni, Feena Renata (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2007)
This paper draws the ability of financial ratio as an earning predictor of property companies at Jakarta Stock Exchange (JSX). Moreover this research tries to find which is significant distinction between financial ratios to property companies This research is conducted by hypotesis and analyzed by discriminant analysys. As result, financial ratios be able to predict property companies earning in JSX with the grouping accuraly is 65.74 % (wilk's lamda: 0.881 and chi 'square: 13.262) than, by stepwise method, the result shows that ROA and current ratio are different.